2016
DOI: 10.1055/s-0042-116488
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of narrow band imaging magnifying colonoscopy for assessing ulcerative colitis-associated cancer/dysplasia

Abstract: Background and study aims: Colitis-associated cancer/dysplasia (CC/D) can affect the life expectancy of patients with ulcerative colitis (UC). Although the utility of magnifying chromocolonoscopy has been shown, the use of optical magnification with narrow band imaging (NBI) for distinguishing CC/D from non-neoplastic lesions in patients with UC has not been reported. We evaluated whether endoscopic findings are distinguishing and thus assessed the clinical usefulness of NBI magnification for differentiating U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
(54 reference statements)
1
36
0
1
Order By: Relevance
“…found that dysplasia was characteristically darkened by obvious capillary vessels. Nishiyama et al . reported that irregular/amorphous surface patterns were useful for differentiation between UCAN and non‐neoplastic lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that dysplasia was characteristically darkened by obvious capillary vessels. Nishiyama et al . reported that irregular/amorphous surface patterns were useful for differentiation between UCAN and non‐neoplastic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…East et al 17 found that dysplasia was characteristically darkened by obvious capillary vessels. Nishiyama et al 18 reported that irregular/amorphous surface patterns were useful for differentiation between UCAN and non-neoplastic lesion. Regarding MC, Kiesslich et al 19 showed that types III, IV and V pit pattern under MC, which were initially proposed for the diagnosis of neoplasm in non-UC subjects, 12,13 were suggestive of dysplasia even in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…reported that a tortuous surface structure on NBI magnification might serve as a clue for the identification of dysplasia in UC patients. Nishiyama et al . suggested irregular and amorphous surface patterns as key findings on NBI for distinguishing CC/D from non‐neoplastic lesions.…”
Section: Characterizationmentioning
confidence: 99%
“…Nishiyama et al 9 suggested irregular and amorphous surface patterns as key findings on NBI for distinguishing CC/ D from non-neoplastic lesions. Recently, Sano et al established the JNET classification system for colorectal tumors, although whether or not JNET is useful for discriminating CC/D from non-neoplastic lesions and from sporadic tumors remains unclear.…”
Section: Nbimentioning
confidence: 99%
“…Several endoscopic imaging techniques have been studied regarding their ability to differentiate dysplastic from non-dysplastic mucosa in patients with longstanding colitis. Besides CE, [8][9][10][11][12] these include advanced imaging techniques as i-Scan 10 , autofluorescence imaging (AFI), 13 narrow band imaging (NBI) 8,[13][14][15] and confocal laser endomicroscopy (CLE). 16,17 It is important to differentiate between dysplastic and non-dysplastic lesions endoscopically as only dysplastic lesions need to be removed to prevent CRC development.…”
Section: Introductionmentioning
confidence: 99%